Goodbye, Mr. Chips - Ross, Herbert 1927-2001; Jacobs, Arthur P. 1922-1973; hamilton, James 1900-1954 (MGM/UA Home Video, 1969)
Lawrence of Arabia, as the shy, dedicated English schoolmaster who becomes a hero to his students. As Katherine, who give up her glamorous life as a London music hall actress to become his bride, popular singer Finian's Rainbow brings a wonderful char, and spontaneity to her role.